Variations on the Topic for a Possible History of Critical Thought. Notes on Nicolas of Autrécourt, Hume, and Husserl (Doctor Virtualis, 2025)
The article aims to delve into Mario Dal Pra’s project for a history of critical thought, outlined in his studies on Greek scepticism, medieval thinkers who raised critical or sceptical issues (John of Salisbury and Nicholas of Autrécourt), and David Hume. After a section dedicated to the notion of critical thought in the monograph on Nicholas of Autrécourt, the article discusses the hypothesis of considering Edmund Husserl as part of an extension of Dal Pra’s history of critical thought, based on his relevance in the editorial project of the Collana di Filosofia (Franco Angeli, 1981-1991), directed by Dal Pra. The critical need for a way of thinking capable of tracing the flow of experience and the world – without falling into metaphysical frameworks that hinder thought or scepticism that relinquishes any constitutive grasp on what can be known – thus seems to outline a common thread connecting thinkers so distant in time, a connection that Dal Pra captured both in his monographs and in the philosophical series.
Keywords: Critical thinking; Mario Dal Pra; Nicholas od Autrécourt; Edmund Husserl; theory of knowledge